Rheological Properties of Wheat Flour Dough as Affected by Addition of Whey and Soy Proteins - Ammar, Abdalla S.; Salem, Samir A.; Badr, Farid H. (Pakistan Journal of Nutrition, 2011)
Dairy by-products and soy proteins are considered natural functional additives having the ability to interact with the starch and gluten network in a dough system. The effects of whey protein (i.e., acid whey, sweet whey, retentate of whey by Reverse Osmosis (R.O), the permeate, pasteurized acid whey, pasteurized sweet whey and whey protein concentrate)and soy protein (raw soy milk, sterilized soy milk, soy protein isolate) addition on dough rheology were studied using Farinograph. The addition of whey protein concentrated by R.O (retentate) exhibited the highest ability to increase water absorption, dough stability, dough development time and time to breakdown of the dough (72.8%, 8.7, 7.7 and 10.0 min, respectively) followed by pasteurized sweet whey and whey protein concentrate. Also, the effect of added raw soy milk was the best on the studied rheological properties (63.2%, 10.3, 6.7, 10.8 min, respectively) of the dough.